Substrate specificity of recombinant human immunodeficiency virus integrase protein. - LaFemina, R L (1991)
Recombinant human immunodeficiency virus type 1 (HIV-1) integrase (IN) produced in Escherichia coli efficiently cleaves two nucleotides from the 3' end of synthetic oligonucleotide substrates which mimic the termini of HIV-1 proviral DNA. Efficient cleavage was restricted to HIV-1 substrates and did not occur with substrates derived from other retroviruses. Mutagenesis of the U5 long terminal repeat (LTR) terminus revealed only moderate effects of mutations outside the terminal four bases of the U5 LTR and highlighted the critical nature of the conserved CA dinucleotide motif shared by all retroviral termini. Integration of the endonuclease cleavage products occurs subsequent to cleavage, and evidence that the cleavage and integration reactions may be uncoupled is presented. Competition cleavage reactions demonstrated that IN-mediated processing of an LTR substrate could be inhibited by competition with LTR and non-LTR oligonucleotides.